Resilience of Muslimah Sex Workers: Fulfilment of Children's Rights Based on Fiqh Hadhanah and the Child Protection Law - Siti Rohmah; Fadil SJ; Erfaniah Zuhriah (Justicia Islamica, 2024)
This research study aims to further explore and delve into the resilience efforts of Muslimah sex workers in fulfilling their children's rights as mandated by Hadhanah jurisprudence and the Child Protection Law, which has become a living law in society. This is socio-legal research with a case study in Wisata Karaoke (ex-localization), Suko, Malang, Indonesia. The method of data collection used in this study is in-depth interviews with four muslimah prostitutes who have children, observation, and documentation. The results of this study indicate that Muslimah sex workers employ two resilience models in fulfilling their children's rights. The first resilience model involves placing their children in Islamic boarding schools (pesantren), considered authoritative childcare institutions. The second resilience model consists of entrusting their children to immediate family members, such as grandparents and aunts, who are perceived to be free from negative influences like promiscuity and alcohol consumption, which are commonly associated with the world of prostitution. Both resilience models are based on mitigation efforts to prevent their children from falling into the same cycle of prostitution as their mothers. This research contributes to becoming new policy material for scholars, government, legislators, and academics in initiating the formation of childcare institutions around ex-localizations as a guarantee of continuity, protection, and fulfillment of the rights of abandoned prostitutes' children.